2007
DOI: 10.1007/s10585-007-9057-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Hif-1 in desferrioxamine-induced invasion of glioblastoma cells

Abstract: Glioblastoma multiforme are highly invasive brain tumors. Experimental approaches focus on unravelling the mechanisms of invasion, this being a major reason for the poor prognosis of these tumors. Our previous results hinted towards involvement of the iron metabolism in invasion. In this study, we examined the effect of iron depletion on the invasive phenotype of glioblastoma cells. Transwell Matrigel invasion assays were used to monitor iron-dependent invasion of human glioblastoma cell lines U373MG and DBTRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…23 MMP-2 transcription is up-regulated during HIF-1α stabilization, which does not increase MMP-9 levels; similar to what we saw in our study. 24, 25 Moreover, multiple downstream targets of HIF-1α are up-regulated during anti-angiogenic therapy. 18 Based on these data, we evaluated HIF-1α expression in U251 glioma cells and found it to be up-regulated as early as 8 hours post therapy (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…23 MMP-2 transcription is up-regulated during HIF-1α stabilization, which does not increase MMP-9 levels; similar to what we saw in our study. 24, 25 Moreover, multiple downstream targets of HIF-1α are up-regulated during anti-angiogenic therapy. 18 Based on these data, we evaluated HIF-1α expression in U251 glioma cells and found it to be up-regulated as early as 8 hours post therapy (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudopalisades around necrotic foci, a common feature of high-grade gliomas, are severely hypoxic and linked to waves of glioma cells actively migrating away from such oxygen-deficient regions [83][84][85]87]. Experimental studies further suggest that tumour hypoxia results in increased glioma cell migration and invasion, and strongly correlates with tumour malignancy [39,88,89]. The exact pathophysiological factors and mechanisms underlying hypoxia-induced cell migration in gliomas are still not known, and further investigation is required to understand the complex molecular pathways involved in hypoxic responses and metabolic control by glioma cells.…”
Section: Hypoxia-induced Migrationmentioning
confidence: 99%
“…In fact, the effect of iron depletion on activation of HIF-1␣ has been linked to the stimulation of tumor angiogenesis and resistance to chemotherapy. For example, Elstner et al, (2007) showed that DFO-induced iron depletion significantly enhanced glioblastoma cell invasion in vitro. However, apart from its tumor-stimulating activity, HIF-1␣ can also potentially have antitumor effects by up-regulating the pro-apoptotic molecule BNIP3 (Bruick, 2000) and the potent tumor suppressor p53 (An et al, 1998).…”
Section: Identification Of Novel Iron-regulated Molecules 453mentioning
confidence: 99%